Corema album (L.) D. Don Phenological Growth Stages according to Extended BBCH Scale - Jacinto, João (2022)
The wild dioecious plant Corema album, endemic to the Atlantic coast of the Iberian Peninsula, has potential to become a new crop and to integrate the berry fruit market. Due to its potential, the aim of this study was to propose a BBCH (Biologische Bundesanstalt, Bundessortenamt and CHemical Industry) scale for the species. Based on field observation, the principal growth stages were described and sequentially established. Photographs and stereomicroscope acquisition software were used to illustrate the phenological stages of male and female plants. The scale includes seven principal stages starting with bud development (stage 0), followed by leaf development (Stage 1), main stem elongation (Stage 3), inflorescence emergence (Stage 5), flowering (Stage 6), fruit development (Stage 7) and ending with fruit maturation (stage 8), with mesostages for male and female inflorescence (stage 5) and flower development (stage 6). Through field observations carried out in plants in different growth conditions, the proposition of this extended BBCH scale was made, to have a standardized system for Corema album phenological stages. This study will have an application especially in fields of agronomy and plant breeding and will also be a stepping stone for the inclusion of this species as a novelty crop in a nearby future